Penerapan Metode Partisipatif 5W-1H dalam Pendampingan Legalitas dan Digitalisasi Manajemen UMKM Jamu Herbal Yunaz Herbaroota - Diaz Agdiansyah Hendra Kusuma; Dandy Akhbaris Raditya; Christian Juan Manurung; Muhammad Adam Fadhulullah; Kristanto Pramudito Respati; Azfar Malik Bin Usman; Tri Siwi Agustina; Elsa Yustika Putri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy, contributing 60% to GDP and employing nearly 97% of the total workforce. However, many MSMEs still face cross-functional challenges that hinder their growth and competitiveness. This community service activity focuses on Yunaz Herbaroota, a traditional herbal beverage (jamu) MSME located in Surabaya, East Java, which faces challenges in digital marketing, human resource competency, operational standardization, and financial management. This topic was chosen considering the growing potential of the herbal beverage market—with a global market value of USD 93.22 billion in 2022—and the urgency of mentoring MSMEs to be able to compete sustainably in the digital era. This community service uses a participatory method that actively involves business owners in the problem identification and resolution process, as well as the 5W+1H method for systematic information gathering. Business model analysis is conducted using the Business Model Canvas (BMC) approach to comprehensively map business conditions and formulate strategic recommendations. The results of the community service activities include the preparation of production requirement letters and sales price adjustment letters as supporting instruments for business financial management, as well as increasing the number of Instagram followers through content produced during the mentoring period. This activity is expected to strengthen Yunaz Herbaroota's capacity in digital marketing, operations, and finance, enabling sustainable growth and expanding its market share.